Suramin inhibits PDGF-stimulated receptor phosphorylation, proteoglycan synthesis and glycosaminoglycan hyperelongation in human vascular smooth muscle cells - Little, Peter J.; Rostam, Muhamad Ashraf; Piva, Terence J.; Getachew, Robel; Kamato, Danielle; Guidone, Daniel; Ballinger, Mandy L.; Zheng, Wenhua; Osman, Narin (Wiley, 2013)
Objectives Suramin is a polysulfonated naphthylurea with antiparasitic and potential antineoplastic activity. Suramin’s pharmacological actions, which have not yet been fully elucidated, include antagonism of the action of platelet-derived growth factor (PDGF) at its receptor. We investigated the effects of suramin on PDGF-stimulated proteoglycan synthesis. Methods Human vascular smooth muscle cells (VSMCs) were incubated in the presence and absence of PDGF and suramin with [3H]thymidine or 35SO4 as radiolabels. Mitogenic response was determined by [3H]thymidine incorporation. PDGFb receptor phosphorylation was assessed by western blotting. Proteoglycan size and glycosaminoglycan chain synthesis and size were determined by sodium dodecyl sulfate–polyacrylamide gel electrophoresis. The Alphascreen phosphotyrosine assay kit was used to investigate PDGFb receptor tyrosine kinase inhibition by suramin. Key findings Suramin decreased PDGF-stimulated proliferation, proteoglycan synthesis and GAG chain hyperelongation. Suramin also directly inhibited PDGFb receptor kinase activity as well as PDGFb receptor phosphorylation in intact VSMCs. Conclusions These data show that inhibition of PDGFb receptor phosphorylation in intact cells is necessary to define a fully active PDGF antagonist. They also confirm that PDGFb receptor kinase activity is necessary for PDGF-mediated atherogenic changes in proteoglycan synthesis and support efforts to develop PDGFb receptor antagonists as potential anti-atherosclerotic agents.